THE MOOD TYPES ANALYSIS IN SCRIPT OF RM’s SPEECH AT THE UNITED NATION - Rahmawati, Resti; Suprijadi, Dasep (PROJECT (Professional Journal of English Education), 2021)
This research discussed mood type analysis in script conveyed by Kim Nam Joon, better known under his performing name RM, leader of BTS (Bangtan Boys) at the United Nation about UN’s Youth 2030 strategy. BTS get chosen as a UNICEF ambassador to front the “Love Myself” campaign in November 2018, which was part of UNICEF’s #ENDviolencecampaign. The objectives of this research are to identify the mood type and describe the interpretation of mood types. The researcher collected the data from The UNICEF website to get the script of the speech and this research used a qualitative descriptive method, which means the researcher analyzed the script. The speech consist of 719 words and 73 clauses, from the data, the researcher found three kinds of the mood types in this script, there are 63declarative, 3 interrogative, and 7Imperative. The result, the researcher concluded that RM’s speech used declarative.Keywords: BTS, Systemic Functional Linguistic, Interpersonal, Mood analysis